Experimental Research and Performance Analysis of a Phase-change Cold Thermal Energy Storage Unit for Emergency Cooling in Air-cooled Modular Data Centers - Huang Bin; Zheng Zi; Lu Gaofeng; Zheng Chunyuan; Li Bin; Zhai Xiaoqiang (Zhileng xuebao)
An approach based on phase-change cold thermal energy storage is proposed for the emergency cooling of an air-cooled modular data center to improve its operational reliability. An experimental setup was built for the cold thermal energy storage unit. The influence of various inlet temperatures on the charging and discharging process of the cold thermal energy storage unit was investigated. In addition, sensitivity analysis was performed on the length, height, spacings of the arcuate fins, and spacings of cold thermal energy storage plates in the unit. The results demonstrate that the experimental cold thermal energy storage unit can meet the emergency cooling demand for at least 5 min. The height of the arcuate fins indicated the greatest influence on the comprehensive heat transfer performance, followed by the fin length. The spacings of the fins and cold thermal energy storage plates have a trivial effect. When the fin height of the experimental cold thermal energy storage unit was reduced from 2.0 mm to 1.5 mm, the comprehensive heat transfer performance is improved by 57%.